1998
DOI: 10.1161/01.str.29.6.1167
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Artery Pressure and Venous Drainage Pattern Are Primary Determinants of Hemorrhage From Cerebral Arteriovenous Malformations

Abstract: Purpose-The purpose of this study was to define the influence of feeding mean arterial pressure (FMAP) in conjunction with other morphological or clinical risk factors in determining the probability of hemorrhagic presentation in patients with cerebral arteriovenous malformations (AVMs). Methods-Clinical and angiographic data from 340 patients with cerebral AVMs from a prospective database were reviewed. Patients were identified in whom FMAP was measured during superselective angiography. Additional variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(79 citation statements)
references
References 33 publications
3
74
0
2
Order By: Relevance
“…All factors that contribute to venous hypertension are likely to increase the potential risk of intracerebral haemorrhage (ICH). The number of draining veins appears to have an inverse relation to venous pressure and thus to haemorrhagic risk [10][11][12]. Venous stenosis is more commonly seen in patients presenting with ICH [13,14].…”
Section: S Chakraborty P Eldridge and H C Nahser E130mentioning
confidence: 99%
“…All factors that contribute to venous hypertension are likely to increase the potential risk of intracerebral haemorrhage (ICH). The number of draining veins appears to have an inverse relation to venous pressure and thus to haemorrhagic risk [10][11][12]. Venous stenosis is more commonly seen in patients presenting with ICH [13,14].…”
Section: S Chakraborty P Eldridge and H C Nahser E130mentioning
confidence: 99%
“…Since the pioneers in the early 1960s reported using methyl methacrylate to embolize the feeding pedicle to treat AVMs, a considerable evolution of microcatheter tools, embolization materials and techniques has proved the success of embolization. Onyx is a new embolization material that has gradually been adopted for AVM embolization during the past decade, and some authors have already reported their initial experiences in the treatment of AVMs with Onyx [11][12][5][6][7][8][9][10][11][12][13][14][15][16]19,21,23,[25][26][27][28] . As mentioned in these articles, Onyx is a nonadhesive agent with controllable endovascular behavior, which allows more precise nidus penetration creating a solid cast, the overall initial complete obliteration rate of intracranial AVMs with Onyx is rela-tively high compared with that of other embolic agents 7,28 .…”
Section: Discussionmentioning
confidence: 99%
“…But if the AVMs are small or supplied by a small number of branches, we should embolize the AVMS as completely as possible. Duong et Al 6 reported that high arterial input pressure and venous outflow restriction (exclusively deep venous drainage) were the most powerful risk predictors for hemorrhagic AVM presentation.…”
Section: Inflow-outflow Imbalancementioning
confidence: 99%
“…17 Variants that were reported to be predictive of BAVM rupture but were not expanded in the recommended protocol were defined with reference to previous studies. [18][19][20] BAVM location was dichotomized into deep (basal ganglia, thalamus, cerebellum, and corpus callosum) and superficial (all other locations). A posterior fossa location was defined as brain stem, cerebellum, or both.…”
Section: Neuroradiologic Reviewmentioning
confidence: 99%